Deltamethrin Impregnated Bed Nets in a Malaria Control Program in Chabahar, Southeast Baluchistan, I.R. Iran - SH Moosa-Kazemi; H Vatandoost; A Raeisi; K Akbarzadeh (Tehran University of Medical Sciences, 2007)
A field trial was carried out in the Chabahar District of Sistan and Baluchistan Province, southeastern Iran on the efficacy of mosquito nets treated with a suspension formulation of deltamethrin (K-O THRIN®) against malaria vectors. Treated nets were used in three villages, and in the two control villages, one used untreated nets and the other used indoor spraying with deltamethrin (WP 10%), without nets. Treatment of polyester mosquito net with a target dose of 25 mg/m2 active ingredi¬ent, carried out in mid-April 2005. Bioassays repeated on domestically used nets over 7 months showed persistence of al¬most 100% mortality of Anopheles. stephensi over this period. Adult mosquitoes were collected by pyrethroid space spray catch of living quarters and stables, cattle bait and pit shelter catches. Overall, An. culicifacies Giles s.l predominated (49.8%), followed by An. stephensi Liston s.l.(36.9%), An. pulcherrimus Theobald (7.3 %), An. dthali Patton (5.7% ) and An. fluviatilis James (0.3%). Acknowledge, Attitude and Practice (KAP) study showed that about 97% of respondents in communities agreed that they would like to participate in malaria control activities such as personal protection using im¬pregnation bed net. Therefore, in planning for future large scale trials, comparison of new compounds and formulations such as tablets and long lasting insecticides impregnated bed net is recommended.